Personality traits and body image: The moderating role of breast surgeries - Romanowska, Daria; Potemkowski, Andrzej; Michałowska, Sylwia (Kultura-Społeczeństwo-Edukacja, 2024)
Being a particular part of the female body, the breasts have a number of important functions, and the evaluation of their shape is emotionally linked to the nature of this area. Surgical operations focused on the aesthetic aspect and, first and foremost, on the health aspect, are of interest to both psychologists and physicians. The objective of the present study was to assess the relationship between personality traits and body evaluation, taking into account the moderating role of breast surgeries, including mastectomy, breast reconstruction and breast reduction. The study was conducted in Poland on 121 women. The study group showed a relationship between personality traits and body self-image. Also, it was observed that there exists a statistically significant moderating effect of the type of surgery on the relationship between individual personality traits and dimensions of body evaluation on the part of female patients. These results provide a more complete understanding of the emotional experience of female patients undergoing breast surgery.